Customer value perception: cross-generational preferences for wine. Issue 7 (1st July 2014) - Wiedmann, Klaus-Peter; Behrens, Stefan; Klarmann, Christiane; Hennigs, Nadine
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – A deeper understanding of the key drivers of consumer wine perception is a major challenge in the domain of wine marketing. The purpose of this paper is to examine the various dimensions of customer-perceived value that lead the customers – in general and divided into different age groups – to choose and consume a certain wine. Design/methodology/approach – In the exploratory study context of examining value-related consumer attitudes and behavioural effects, the drivers and outcomes of wine consumption based on a cross-generation sample, PLS path modelling was considered for the empirical tests of our hypotheses. Findings – Though there exist differences between Generation X and Generation Y consumers, the empirical results are supportive of the hypothesized positive relations between financial, functional, individual and social perceptions that influence the desire for and the consumption of wine. Research limitations/implications – For future research, the findings presented in the paper support the importance of enlarging the size of the sample and collecting data in different countries to compare the results on an international level. Practical implications – Successful wine marketing strategies should focus on the customer's subjective expectations and individual value perceptions by addressing the specific value aspects that are highly relevant for consumer loyalty. Originality/value – The study results are valuable for researchers, managers and marketers because they address the question of how to measure and forecast the perceived value with the greatest influence on consumers' wine choices.